Glycolic acid functionalized chitosan-Au-Fe3O4 hybrid nanoparticle based nanohybrid scaffold for drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2013)
The research on biomedical applications of nanoparticles has seen an upsurge in recent years due to their unique capabilities in treatment of ailments. The present paper reports the synthesis of Au-Fe3O4 hybrid nanoparticles. The formation of these nanoparticles was confirmed by transmission electron microscopy (TEM) and physical property measurement system (PPMS). Next step of this paper reveals potential use of novel hybrid of chitosan-g-glycolic acid and Au-Fe3O4 hybrid nanoparticles in controlled drug delivery and tissue engineering applications. Grafting of glycolic acid and drug loading in porous scaffold was characterized by Fourier transform infrared spectroscopy. The nanohybrid scaffolds were found to be stable regardless of pH of the medium and play a key role in cell adhesion, proliferation and migration. Au-Fe3O4 hybrid nanoparticles reinforcement was found to control the drug (cyclophosphamide) release rate in phosphate buffer saline solution (pH 7.4). Therefore, Au-Fe3O4 hybrid nanoparticles are viable additive for formulating sustained drug delivery systems based on glycolic acid grafted chitosan. The cell proliferation profile also shows that prepared nanohybrid is biocompatible providing suitable substrates for tissue engineering. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Au-Fe3O4 hybrid nanoparticles; Chitosan Glycolic acid grafting; Drug delivery system; Physical property measurement system